Nilai-nilai Pendidikan Karakter Dalam Buku Teks Muthalaâ€™ah dan Implikasinya Dalam Pembelajaran Maharah Qiraah - Hidayatillah, Baiq Wahyu Diniyati; Atiq, Abdian Akbar (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2023)
Arabic has grammatical complexity with high sentences, many people who learn Arabic have difficulty understanding more complex Arabic texts, one of which is literary texts. This paper aims to understand the values of character education in muthala’ah textbooks based on Roland Barthes’ semiotic approach and find out their implications for maharah qiraah learning. This type of research is a qualitative library (library research) that uses data sources that are relevant to the title. The most important finding in this study is the meaning of the text in the book muthala’ah volume 2 based on Roland’s semiotic study which includes the meaning of structural narrative analysis by examining the lexia included in the reading codes; hermeneutic, semimic code, symbolic code, proaretic code, and gnomic code. The codes contain the meaning of morality. Implications of character education values; caring, cooperation, honesty, openness, a sense of responsibility in maharah qiraah learning can help students gain meaningful learning and succeed in acquiring good Arabic reading skills.